2011
DOI: 10.1007/s12975-011-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Postischemic Dehydroascorbic Acid Administration in a Large-Animal Stroke Model

Abstract: Dehydroascorbic acid (DHA), a blood-brain barrier transportable form of ascorbic acid, confers robust neuroprotection following murine stroke. In an effort to translate this promising neuroprotective strategy into human clinical trial, we evaluated postischemic DHA administration in a large-animal stroke model. Thirty-six adult male baboons were initially randomized to undergo transorbital craniectomy to induce transient cerebral artery occlusion and to receive postischemic dosing of either 500 mg/kg of DHA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Observational studies in human patients showed that increases in plasma levels of vitamin C were correlated with reduced incidence of stroke [123]. In animal studies, although 4 weeks pre-treatment with vitamins C and E diminished the degree of lipid peroxidation and reduced infarct volume after middle cerebral artery occlusion [124], administering dehydroascorbic acid after arterial occlusion in baboons with transient cerebral artery occlusion was not able to significantly decrease lesion volume [125]. Similarly, human stroke trials with antioxidant vitamin supplements showed no benefits, neither in the acute setting [126] nor in prevention [127].…”
Section: Upregulation Of Endogenous Antioxidant Defensesmentioning
confidence: 99%
“…Observational studies in human patients showed that increases in plasma levels of vitamin C were correlated with reduced incidence of stroke [123]. In animal studies, although 4 weeks pre-treatment with vitamins C and E diminished the degree of lipid peroxidation and reduced infarct volume after middle cerebral artery occlusion [124], administering dehydroascorbic acid after arterial occlusion in baboons with transient cerebral artery occlusion was not able to significantly decrease lesion volume [125]. Similarly, human stroke trials with antioxidant vitamin supplements showed no benefits, neither in the acute setting [126] nor in prevention [127].…”
Section: Upregulation Of Endogenous Antioxidant Defensesmentioning
confidence: 99%
“…In contrast, high-dose vitamin E supplements have been suggested to increase all-cause mortality [124,125]. Administration of dehydroascorbic acid (DHA), a blood-brain barrier transportable form of vitamin C, and EPC-K1, a phosphate diester of vitamins C and E, ameliorated outcomes in a mouse MCAO model, while preclinical administration did not show a neuroprotective effect [126][127][128]. Apart from antioxidant vitamins, other studies based on free radical scavengers such as edaravone, N-acetylcysteine, and NXY-059 have revealed improved neurological outcomes in rodent and primate models, but the performance of exogenous antioxidants in recent clinical trials has been inconsistent [129][130][131][132].…”
Section: Mitochondria and Ros Production In Ismentioning
confidence: 99%
“…One form of vitamin C, ascorbic acid, was found to protect newborn rat brain from HI injury [ 173 ]. In a large animal stroke model, the administration of dehydroascorbic acid did not significantly decrease infarct volume or improve neurological outcome and the study was terminated early [ 174 ]. In a recent study however, it was found that 4 weeks of pre-treatment of stroke-prone spontaneously hypertensive rats with vitamins C and E lowered levels of lipid peroxidation and significantly lowered infarct volume following MCAO [ 175 ].…”
Section: Antioxidant Strategiesmentioning
confidence: 99%